PENINGKATAN KINERJA IPAL LUMPUR AKTIF DENGAN PENAMBAHAN UNIT BIOFILTER (STUDI KASUS IPAL PASARAYA BLOK M, KAPASITAS 420 M3/HARI) - Ikbal, Ikbal (Jurnal Air Indonesia, 2016)
WWTP system selection is determined by the characteristics of the waste water. Wrong WWTP system will cause quality of treated water difficult to meet the Quality Standard and also lead to high operating costs. Added Biofilter unit to Pasaraya Blok M WWTP system, provide very encouraging result. For more than one year, WWTP operation always in good performance. The concentration of BOD, COD and KMnO4 can be derived more than 90%, as well as TSS can be reduced over 90%. The concentration of all pollutants in treated water far below the government quality standards, so it’s not polluted to the environment. WWTP Pasaraya Blok M already has Liquid Waste Disposal License Certificate (IPLC), as a legal statement or certificate that allowed them to dispose of treatment water into the water body. Pasaraya Blok M also performs self-monitoring for operational of WWTP and periodic analysis to an accredited laboratory. Keywords : domestic waste water, waste water treatment plants, organic pollutants, activated sludge, biofilter, treatment efficiency